Effect of Cationic/Anionic Mixed Micelles on Reaction Kinetics of Alkaline Hydrolysis of Crystal Violet - Yilma, Qidist; Negussa, Dunkana; Ravichandran, Y. Dominic (Asian Journal of Chemistry, 2019)
Kinetics of alkaline hydrolysis of crystal violet, a triphenylmethane dye in the micellar environment of cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfonate (SDS) and binary mixtures of these surfactants was studied. The regression parameters, together with rate constants and binding constants were obtained by analyzing the rate surfactant profiles using cooperativity model. It was observed that the reaction was catalyzed by both surfactants. The catalytic factor increased by 10 times in SDS and 38 times in CTAB indicating that binding of crystal violet to the micellar surface is stronger in pure CTAB than SDS but the strength drastically reduced in the mixtures of the surfactants. Reduction of binding constant became more important as the mole fraction of CTAB was improved in the mixture. The kinetic data were investigated using Piszkiewicz model and Raghavan-Srinivasan model. The data obtained from the models were in good agreement with the experimental values.